Price Controls : Good Intentions, Bad Outcomes - Guenette, Justin-Damien (World Bank, Washington, DC, 2020)
The use of price controls is widespread across emerging markets and developing economies, including for food and key imported and exported commodities. Although they are sometimes used as a tool for social policy, price controls can dampen investment and growth, worsen poverty outcomes, cause countries to incur heavy fiscal burdens, and complicate the effective conduct of monetary policy. Replacing price controls with expanded and better-targeted social safety nets, coupled with reforms to encourage competition and a sound regulatory environment, can be pro-poor and pro-growth. Such reforms need to be carefully communicated and sequenced to ensure political and social acceptance. Where they exist, price control regimes should be transparent and supported by well-capitalized stabilization funds or national hedging strategies to ensure fiscal sustainability.